Civil protection for the right to privacy regarding the use of drones - Yaseen, Hajar (Humanities Journal of University of Zakho, 2023)
There is no doubt that the recent tremendous progression and advancements in technology, especially drone technology, have paved the way for transgressing on individual rights and for violating personal privacy around the world. Drone technology, as one type of aircraft technology, is sweeping the modern world. The unrestrained use of drones and its negative effects on different life aspects; whether military, civil, or commercial, raises a number of legal issues, whether related to national safety and the protection of the right to privacy and air navigation, urged many countries to legislate laws and regulate the use of drones within the frames of laws, to register them, and set certain legal conditions for using them. However, legislators in Iraq and Iraqi-Kurdistan have not yet paid attention to this issue. This stresses the necessity of legislating laws related to drone technology and uses to protect the right to privacy and the civil liability arising therefrom, with a focus on the preventive aspect by imposing certain obligations on drone users.